A importância do professor de educação física nos anos iniciais do ensino fundamental - Carmem Elisa Henn Brandl; Inácio Brandl Neto (Universidade Estadual do Oeste do Paraná, 2015)
A project named "Physical Education in the of elementary school: a proposal for social inclusion through motor activities", which was part of a State Government program " University Without Borders " was developed in two cities with low HDI (Human Development Index) in west Paraná State, where physical education classes began to be taught by licensed teachers, rather than teachers with other backgrounds. The aim of this paper is to investigate the importance of the licensed Physical Education teacher, with a graduate degree, to teach classes in the early years of elementary school, taking into account the experience acquired in these municipalities. The methodology of this descriptive research was guided to two aspects. First, in the form of standardized tests with 340 children; and second, in the form of a questionnaire conducted with parents (16), directors (2), teachers (11) and students who attended the project (340). The test results showed that there was an increase of children's development in relation to the initial diagnosis (beginning of school year) when compared to that achieved at the end of the year, considering the standard scores for dribbling, throwing, kicking, tests of balance, body structure, spatial awareness, fine and gross motor skills. The questionnaires results demonstrated that children improved in social-affective, cognitive and motor aspects, as a result of lessons ministered by teachers of the project.